Regional Economic Outlook, October 2008, Sub-Saharan Africa. (Regional Economic Outlook; October 2008, 2008)
Sub-Saharan Africa's prospects have deteriorated somewhat and the risks have increased, according to this report. Growth in the region is projected to dip to 6 percent in 2008 and 2009. The fall is due mainly to the global food and fuel price shock, which has weighed particularly on growth in oil-importing countries, and to the global financial market turmoil, which has slowed global growth and demand for Africa's exports. Inflation is expected to rise to 12 percent in 2008, mainly on account of the food and fuel price shock. As a result of rising prices, particularly of food, poverty may well be on the increase in 2008. In 2009, inflation should ease to 10 percent, helped by recent commodity price declines. There are significant risks to the outlook related to a potentially deeper and longer period of global financial turmoil and resulting slowdown in global activity, and substantial uncertainty concerning commodity prices.